Insights for Systems Security Engineering from Multilayer Network Models. Issue 1 (20th September 2021) - Williams, Adam D.; Birch, Gabriel C.; Caskey, Susan A.; Fleming, Elizabeth S.; Gunda, Thushara; Adams, Thomas; Wingo, Jamie
Abstract: Next‐generation approaches for systems security engineering will need to address challenges stemming from complex risk environments, innovative adversaries, and disruptive technologies—particularly for high consequence facilities (HCF). Key insights from complexity, systems, and network theories—and support from subject matter expert (SME) elicited empirical data—support using a multilayer network model for HCF security to address these challenges. Early results of modeling HCF security system performance in terms of multilayer network characteristics seemed to meet the needs expressed in the SME data, provide a suite of mathematically tractable metrics to describe more complex security behaviors, and align with characteristics related to incorporating systems security engineering into the future of systems engineering.